Pokemon adventures. Emerald. Volume 28 - Kusaka, Hidenori; Turnage, Bryant (VIZ Media, LLC, 2015)
Professor Birch sends Sapphire and Ruby to help Emerald find the Wish Pok©♭mon Jirachi, but first Ruby discovers something surprising about Emerald's Sceptile, and everyone learns the true identity of their archnemesis, Guile Hideout.